2006
DOI: 10.1007/s10725-006-9129-z
|View full text |Cite
|
Sign up to set email alerts
|

IAA, ABA, polyamines and free amino acids associated with zygotic embryo development of Ocotea catharinensis

Abstract: The aim of this work was to study morphological and biochemical aspects during zygotic embryogenesis in O. catharinensis, by measuring changes in the endogenous concentrations of proteins, amino acids, polyamines (PAs), indole-3-acetic acid (IAA) and abscisic acid (ABA). Buffer-soluble and insoluble protein contents were determined by spectrometry, and amino acids, PAs, IAA and ABA concentrations were determined by high performance liquid chromatography. Total amino acid accumulation, predominantly asparagine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
14

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 55 publications
(62 reference statements)
2
36
1
14
Order By: Relevance
“…Protein analysis: Protein extracts were prepared in biological triplicates (300 mg FM) for each maturation treatment. Soluble and insoluble proteins were extracted from these cultures according to the method described by Santa-Catarina et al (2006). Soluble proteins were extracted using a phosphate buffer (pH 7.5) containing 50 mM sodium phosphate dibasic, 10 mM 2-mercaptoethanol and 1 mM phenylmethylsulfonyl fluoride (PMSF).…”
Section: Induction Of Embryogenic Culturesmentioning
confidence: 99%
“…Protein analysis: Protein extracts were prepared in biological triplicates (300 mg FM) for each maturation treatment. Soluble and insoluble proteins were extracted from these cultures according to the method described by Santa-Catarina et al (2006). Soluble proteins were extracted using a phosphate buffer (pH 7.5) containing 50 mM sodium phosphate dibasic, 10 mM 2-mercaptoethanol and 1 mM phenylmethylsulfonyl fluoride (PMSF).…”
Section: Induction Of Embryogenic Culturesmentioning
confidence: 99%
“…org). Natural propagation of O. catharinensis through seeds is hindered by its recalcitrancy, which means that seeds cannot be stored over long periods without a serious loss of viability (Silva et al1998;Viana and Mantell 1999;Santa-Catarina et al 2006). …”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that proteomic analysis can generate relevant information towards elucidating the identity of those molecular mechanisms involved in developmental processes. Furthermore, the search is under way to trace biochemical and molecular markers in specific stages of embryogenesis in tree species (Silveira et al 2004;Rossignol et al 2006;Santa-Catarina et al 2006;Silveira et al 2008). The characterization of profiles and changes in protein content during seed development allows for comparing in vitro and in vivo embryo development.…”
Section: Introductionmentioning
confidence: 99%
“…Amino acids determination was carried out according to Santa-Catarina et al (2006). Samples (200 mg) were ground in 6 mL of 80% (v/v) ethanol and concentrated in a SpeedVac.…”
Section: Methodsmentioning
confidence: 99%